Perilaku Konsumen Dalam Pembelian Buah Durian (Studi Kasus Pada Durian By Reza) - Wiwin Alawiyah; Gina Fauziah; Ahmad Dany (Universitas Batangahari Jambi, 2026)
This study provides an overview of consumer preferences and behavior in consuming durian, both in fresh and processed forms, which are influenced by various product and service attributes. The objective of this research is to analyze the characteristics and purchasing behavior of consumers at Durian Jambi By_Reza in Jambi City. The method used in this study is a survey of consumers who have previously made purchases. This business was established in 2021 by Reza, relying on direct supply from local farmers and marketing through both a physical outlet and social media. The results show that most consumers prefer durian priced below IDR 50,000 per fruit, with a preference for medium-sized durians, greenish-yellow in color, and having a sweet and rich taste, along with fast and friendly service. Service is the most important factor influencing purchasing decisions, with an importance value of 36.13%, followed by taste (17.33%), color (16.50%), size (15.23%), and price (14.80%). In addition, consumers perceive the outlet as clean, with prompt and friendly service and a comfortable atmosphere. The conjoint analysis results indicate that the best combination of attributes achieved the highest score of 3.18, while the lowest score was 2.67. The Pearson’s R correlation (0.990) and Kendall’s Tau (0.877) show a very strong relationship between observed and estimated consumer preferences. The model is also significant (0.000 < 0.05), indicating that it can accurately predict consumer preferences